Perampanel-associated Psychiatric Problems - Anil Kakunje; Shivanand Pai; S. Raghavendra (Archives of Medicine and Health Sciences)
Perampanel is a noncompetitive α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid glutamate receptor antagonist used in the management of seizure disorder. Management of uncontrolled seizures is a challenging task. Perampanel is a recent antiepileptic which comes with a warning of causing behavioral and psychological adverse effects. Here, the authors report an interesting case where the perampanel was started to control refractory seizures and the person developed severe behavioral disturbances. The condition warranted a psychiatry referral, and the problems subsided after stopping perampanel. Clinicians need to be vigilant about perampanel-associated behavioral and psychiatric problems which can become a serious clinical concern.